PENGARUH ANGGARAN BELANJA, INFRASTRUKTUR DAN PERTUMBUHAN EKONOMI TERHADAP KETIMPANGAN PEMBANGUNAN PROVINSI KALIMANTAN SELATAN - Zulfaridatul Yaqin, Siti Mutmainah; Yunani, Ahmad; Nur, Muhammad Anshar (At-Taradhi Jurnal Studi Ekonomi, 2018)
This study aims to determine the disparity of economic development between districts / cities and the influence of budgetary variables, infrastructure and economic growth on the inequality of economic development in South Kalimantan Province in 2011 - 2015. The research method used is descriptive quantitative with the analysis tools using the technique of Regional Economic analysis (Williamson Index) and simple regression analysis model. The result of the research shows that the disparity between districts / cities in South Kalimantan Province using Williamson Index within the period of 2011 - 2015 indicates a decreasing disparity that has an average of  0.513 with mining and quarrying sector and 0.310 without mining and quarrying sector. The result of F test shows that the budget expenditure, infrastructure and economic growth simultaneously have significant effect on regional disparity variables and the result of t test shows the budget expenditure and economic growth significantly influence the regional disparity in South Kalimantan Province at the alpha significance level of 0.1 or the level of trust 90 %.